VELOCITIES OF SLOW MIGRATION OF SEISMIC ACTIVITY IN CIS-BAIKAL REGION - Anna V. Novopashina; Vladimir A. San’kov (Геодинамика и тектонофизика)
Three-dimensional space-time diagrams of «logarithm of total energy released by earthquakes» parameter, lgEsum are constructed for regions with stable concentrations of earthquake epicenters in Cis-Baikal region for a period from 1964 to 2002. Based on analyses of such diagrams, areas of slow migration of seismic activity are defined. Estimated are distances, time and velocities of slow migration in the range of the first kilometers – first dozen of kilometers per year.Procedures of seismic data projection and construction of 3D diagrams are described in brief. A general scheme including contours of projection areas is proposed for the Pribaikalie (Fig. 1).Three space-time diagrams are presented as examples of application of the above mentioned procedures. They are constructed for the Middle and Southern Baikal basins and the western part of the NE flank of the Baikal rift system (Fig. 2). Integrated analytical results are presented for all the diagrams which record earthquake migration within the Baikal rift system.We also present a scheme of the zone of slow migrations ranked by dominating velocities (Fig. 3) and a diagram of the migration velocity range. We consider possible causes of slow migration of seismic activity at variable velocities: (1) slow deformation waves spreading in the crust, and (2) independent propagation of the deformation front along active faults.Regulations of migration of strong earthquakes can be useful for definition of timelines and locations of future strong seismic events.